Slope = (7 -1)/(1+2) = 6/3 = 2
equation of <span>point-slope form
y - 1 = 2(x + 2)
hope it helps</span>
543,100.....543,200......543,300
Answer:
![(f o g)(x) = 3x + \frac{2}{3}](https://tex.z-dn.net/?f=%28f%20o%20g%29%28x%29%20%3D%203x%20%2B%20%5Cfrac%7B2%7D%7B3%7D)
Step-by-step explanation:
We have the function
and we have the function
. We want to find g(x) composed with f(x)
Then, the function (f o g)(x) is the same since f(g(x))
That is, you must do x = g(x) and then enter g(x) into the function f(x).
![f(g(x)) = (g(x)) -\frac{1}{3}](https://tex.z-dn.net/?f=f%28g%28x%29%29%20%3D%20%28g%28x%29%29%20-%5Cfrac%7B1%7D%7B3%7D)
![f(g(x)) = (3x + 1) -\frac{1}{3}](https://tex.z-dn.net/?f=f%28g%28x%29%29%20%3D%20%283x%20%2B%201%29%20-%5Cfrac%7B1%7D%7B3%7D)
Simplifying, we obtain:
![(f o g)(x) = 3x + 1 -\frac{1}{3}\\\\(f o g)(x) = 3x + \frac{2}{3}](https://tex.z-dn.net/?f=%28f%20o%20g%29%28x%29%20%3D%203x%20%2B%201%20-%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C%5C%28f%20o%20g%29%28x%29%20%3D%203x%20%2B%20%5Cfrac%7B2%7D%7B3%7D)
Finally. The composite function is:
![(f o g)(x) = 3x + \frac{2}{3}](https://tex.z-dn.net/?f=%28f%20o%20g%29%28x%29%20%3D%203x%20%2B%20%5Cfrac%7B2%7D%7B3%7D)
I think the answer is 17.5 years